Aquatic weeds diversity of Bangladesh Agricultural University Campus, Mymensingh, Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
A study was conducted to find out the biodiversity of aquatic weeds of Bangladesh Agricultural University Campus Mymensingh from January to May, 2016. A total of 39 weed species were identified from the area. Among four common groups of weeds, five species of floating weeds: Eichhornia crassipes, Pistia stratiotes, Azolla pinnata, Lemna minor, Spirodela polyrrhiza,  22 species of emergent weeds: Alternanthera philoxerodies, Ipomea aquatica, Polygonum glabrum, Sagittaria spp., Oxalis corniculata, Marsilea quadrifolia, Commerlina bengalensis, Commelina appendiculata, Ipomea carnea, Nymphaea rubra, Nymphaea nauchali, Leersia hexandra, Scirpus mucronatus, Ludwigia adscendens, Enhydra fluctuans, Trapa natans, Colocasia esculenta, Hygrorayza aristata, Ipomoea spp., Nymphoides aquatica, Typha latifolia, Aponogeton spp., five species of submerged weeds: Hydrilla verticilata, Cartophyllum demersum, Vallisneria spiralis, Najas minor, Vallisnaria spp. and seven species of algae: Microcystis spp., Chara spp., Anabaena spp., Nitella spp., Spirogyra spp., Chlorella spp., Euglena spp. were identified. Various useful and harmful aspects of these weeds were also discussed.Asian Australas. J. Biosci. Biotechnol. 2017, 2 (2), 181-192